The Effect of Interlayer on Water Cut Rise in a Bottom Water Reservoir. (19th August 2021) - Hu, Yunpeng; Zhang, Xiaoling; Ding, Wei; Cheng, Ziyun; Qu, Liangchao; Su, Penghui; Sun, Chunliu; Zhang, Wenqi
Abstract : A bottom water reservoir is universal in all reservoirs in the world. In the exploitation process of the bottom water reservoir, because the reservoir is in complete contact with bottom water, the natural energy supply of the bottom water reservoir is sufficient. At the same time, in the production process, the pressure drop generated by the formation is mainly concentrated near the wellbore, which leads to a short period of waterless oil production, fast water breakthrough, and fast water cut rise, which seriously affects the overall recovery factor and increases the risk of oil filed exploitation. Since the distribution of an interlayer enhances the heterogeneity of the reservoir, it has a prominent impact on the flow of oil and water in the bottom water reservoir. However, people know little about the impact of the interlayer on the bottom water reservoir. In this paper, the mathematical model of two-phase flow in the bottom water reservoir with the interlayer is proposed, and the numerical solution of the model is obtained by a finite element method. The influence of the distribution of the interlayer on the water cut rising law of the bottom water reservoir is analyzed. The results show that the bottom water is blocked by the interlayer and its own gravity and the rising height of the bottom water is limited, so that the interlayer has a significant inhibitory effect on the coning of the bottom water. The closer the interlayer is to the oil-water interface, the faster the water cut will rise; the narrower the interlayer is, the faster the bottom water ridge will advance; when the width of the interlayer is the same as that of the reservoir, the water cone will not appear; the higher the permeability of the interlayer is, the faster the upper body of the water cut will be; when the permeability of the reservoir and the interlayer is over 1000, the influence of the interlayer on the water cut rise is not obvious; the thickness of the interlayer on the water cut rise law has little effect. Finally, through the case analysis, it is proposed that the new horizontal wells should be arranged in the position where the interlayer develops. The findings of this study can help for the better understanding of control laws of the interlayer on the bottom water and providing a crucial theoretical basis for the development of the bottom water reservoir.